FETAL CYTOKINES IN PREGNANT WOMEN WHO HAVE COVID-19 IN THE SECOND TRIMESTER OF GESTATION (World Bulletin of Public Health, 2023)
Of the 387 pregnant women who had COVID-19 and were admitted to the hospital, 23.8% were ill in the first trimester, 49.9% of pregnant women in the second trimester, and the remaining 26.3% of pregnant women in the third trimester. In terms of severity, 51.4% of women had a mild form, 43.2% had a moderate form and 5.4% had a severe form of the disease. The most common extragenital diseases were anemia of pregnant women (58.9%), heart disease in the form of chronic myocarditis (22.7%) and obesity (21.1%). Of the obstetric outcomes in pregnant women with a history of COVID-19, the most common were premature birth, which amounted to 13.7%, and a high incidence of severe preeclampsia, which amounted to 18.3%. The incidence of premature birth in pregnant women with severe COVID-19 at 22-28 weeks was significantly more than 8 times higher than in pregnant women with mild COVID-19.
Keywords: cytokines; fetus